The intimate relationship between structural relaxation and the energy landscape of monatomic liquid metals - Franz Demmel (Nature Portfolio, 2021)
Abstract The characteristic property of a liquid, discriminating it from a solid, is its fluidity, which can be expressed by a velocity field. The reaction of the velocity field on forces is enshrined in the transport parameter viscosity. In contrast, a solid reacts to forces elastically through a displacement field, the particles are trapped in their potential minimum. The flow in a liquid needs enough thermal energy to overcome the changing potential barriers, which is supported through a continuous rearrangement of surrounding particles. Cooling a liquid will decrease the fluidity of a particle and the mobility of the neighbouring particles, resulting in an increase of the viscosity until the system comes to an arrest. This process with a concomitant slowing down of collective particle rearrangements might already start deep inside the liquid state. The idea of the potential energy landscape provides an attractive picture for these dramatic changes. However, despite the appealing idea there is a scarcity of quantitative assessments, in particular, when it comes to experimental studies. Here we present results on a monatomic liquid metal through a combination of ab initio molecular dynamics, neutron spectroscopy and inelastic x-ray scattering. We investigated the collective dynamics of liquid aluminium to reveal the changes in dynamics when the high temperature liquid is cooled towards solidification. The results demonstrate the main signatures of the energy landscape picture, a reduction in the internal atomic structural energy, a transition to a stretched relaxation process and a deviation from the high-temperature Arrhenius behavior of the relaxation time. All changes occur in the same temperature range at about $$1.4 · T_{melting}$$ 1.4 · T melting , which can be regarded as the temperature when the liquid aluminium enters the landscape influenced phase and enters a more viscous liquid state towards solidification. The similarity in dynamics with other monatomic liquid metals suggests a universal dynamic crossover above the melting point.